The Effects of Vocabulary and Grammar Mastery on Students’ Writing Skill in Descriptive Text (Surveys at Private Junior High Schools in Serang Banten) - Haryadi, Rofiq Noorman; Endah, Junaedah; Dalimunthe, Lesnasari (JLE: Journal of Literate of English Education Study Program, 2021)
This research is aimed to get emperical data and analyze the effects of vocabulary and grammar mastery on writing skill in descriptive text at private junior high schools in Serang Banten. This research is done by Kolmogorov-Smirnov method, ANOVA Table, Proportional Correct for testing the item difficulties, by biserial coefficient, and by Kuder Richarsson testing. The research was held at Privates Junior High Schools in Serang Banten. Data collective done by giving test for writing skill (make a composition or an essay about an object description), test for vocabulary mastery (multiplechoice/ 35 items), and test for grammar mastery (multiplechoice/ 35 items) given to class at MTs Al Ma’arif, MTs Nurul Basmallah and MTs Nurul Huda. The result of study identifies there are effects between Vocabulary and Grammar Mastery towards Student’s Writing Skill in Descriptive Text (Fo = 18.748 and Sig = 0,000 < 0,05; coefficient of 0.666 and the coefficient determination of 81.5%). There is effect of Vocabulary Mastery towards Student’s Writing Skill in Descriptive Text (Sig = 0.026 < 0,05 and ttest = 2,301; while ttable = 1,88). There is effect of Grammar Mastery towards writing skill in Descriptive Text (Sig = 0.002 < 0,05 and ttest = 3,656 while ttable = 1,88).